Peran Homiletika Dalam Membangun Pemahaman Alkitab Di Era Globalisasi - Seri Antonius Tarigan; Mawarni Hutagalun; Rahayu Sianturi; Nainggolan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Homiletics, as the art and science of conveying sermons or messages from God's word, has an important role in building understanding of the Bible in the era of globalization. In the context of a modern world full of information and cultural challenges, homiletics must be able to bridge the messages of the Bible with the needs of congregations living amidst global complexity. This research aims to explore how homiletics can adapt to current developments, use a relevant and contextual approach, and remain faithful to the truth of God's word. The method used in this research is a qualitative approach with literature study and analysis of homiletical practices in various church contexts. The research results show that preachers need to understand the needs of the congregation holistically and use creative communication methods, such as the use of digital technology, contextual narratives, and a dialogic approach. In addition, emphasis on the integrity of the preacher and sensitivity to the challenges of globalization, such as the relativism of truth and secularism, are important factors in conveying the Bible's message effectively. This research concludes that homiletics plays a role as a spiritual transformation tool that is relevant in the era of globalization by responding to the challenges of the times through conveying contextual, applicable and inspirational Bible messages. The emphasis on the use of digital media and a contextual hermeneutical approach is expected to help congregations not only understand God's word, but also apply it in everyday life. Homiletics that is relevant in the era of globalization is homiletics that brings God's word to life and has a real impact in an ever-changing world.